Character-based indexing using inverted lists - Knancome, Chouvalit; Boonjing, Veera (My University, 2009)
This research article presents a new character-based indexing algorithm which generates all locations of target text to the inverted list in existed bit form. This algorithm is efficiently to search in the case of streaming character input that needs to immediately response. © 2009 IEEE.
Keywords: Character-based indexing; Inverted index; Inverted lists; Pattern matching; Text indexing